1978
DOI: 10.1111/j.1399-0039.1978.tb01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Monitoring of the Immune Response to Various Allografts in Rats

Abstract: The appearance of activated lymphocytes and antibodies in the circulation of rats was monitored following allogeneic kidney, skin, or combined skin-spleen transplants. Lymphocyte activation was measured by 3H-thymidine incorporation, and antibody by a hemolytic assay. These assays have been developed so that small samples of blood could be used, thus maintaining recipient survival and allowing for daily correlation between the response observed and the fate of the graft. These responses were detected after all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1979
1979
1981
1981

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…All three untreated allograft recipients ( C , D, E) showed both proliferative and antibody responses. As previously shown in the Lewis strain (Smart et al 1978) the peak of the proliferative response as well as the rate of antibody formation was more variable than is seen in DA recipients.…”
Section: Passive Enhancement In the (Da X Lewis) Fl Into Lewis Modelsupporting
confidence: 65%
See 3 more Smart Citations
“…All three untreated allograft recipients ( C , D, E) showed both proliferative and antibody responses. As previously shown in the Lewis strain (Smart et al 1978) the peak of the proliferative response as well as the rate of antibody formation was more variable than is seen in DA recipients.…”
Section: Passive Enhancement In the (Da X Lewis) Fl Into Lewis Modelsupporting
confidence: 65%
“…Studies on allogeneic and isogeneic renal transplant recipients in the (DA x Lewis) F1 into DA and Lewis combinations have indicated that the proliferative response of peripheral lymphocytes is specific, that it invariably precedes rejection, and that its magnitude may be related to the magnitide of subsequent rejection (Smart et al 1978). In 10 of the 11 recipients which have been treated with enhancing antiserum in this study the proliferative response of peripheral lymphocytes and the hemolytic antibody response have been depressed.…”
Section: Disczkssionmentioning
confidence: 58%
See 2 more Smart Citations